Seeking meaning : a process approach to library and information services - Kuhlthau, Carol Collier, 1937- (2004)
"Seeking Meaning was first published in 1993. It has since become a widely used professional resource and required reading in library and information science schools in the United States and abroad. This book offers essential knowledge for anyone providing library and information services. Library and information services for intellectual access - the interpretation of information and ideas within sources - and the process of seeking meaning are detailed. Presented is a theoretical framework for a process approach to library and information services, which was developed in a series of studies of the Information Search Process of users. The framework has helped to illuminate the user's perspective of information seeking, and has offered insights into pressing problems of seeking meaning in an overabundance of information."--Jacket
The Constructive process in library and information science -- Learning as a process -- The Information search process -- Verification of the model of the information search process -- Longitudinal confirmation of the information search process -- Uncertainty principle -- Roles of mediators inthe process of information seeking -- Zones of intervention in the process of information seeking -- Implementing the process approach -- Information search process in the workplace -- Process-oriented library and information services
Includes bibliographical references (pages 211-219) and indexes
Keywords: Reference services (Libraries); Reference services (Libraries) -- United States -- Case studies; Library research; Library research -- United States -- Case studies; Information retrieval; Searching behavior; Reference services (Libraries) -- United States -- Case studies; Library research -- United States -- Case studies; Case studies